National Accounts Statistics: Main Aggregates and Detailed Tables 2013 - United Nations Department of Economic; Social Affairs (United Nations, 2015)
This publication contains detailed official national accounts data for over 200 countries or areas of the World for the years 2001 to 2013. It is a valuable source of information on the state and structure of economies worldwide. The data for each country or area are presented in separate chapters with uniform table headings and classifications as recommended in the System of National Accounts 1993 (1993 SNA). Each country chapter also contains a write-up on the methodology and data sources which are used to compile the national accounts. A summary of the SNA conceptual framework, classifications, and definitions is also. It also contains statistics on gross domestic product.